Kidney recipients with allograft failure, transition of kidney care (KRAFT): A survey of contemporary practices of transplant providers. Issue 9 (12th April 2021) - Alhamad, Tarek; Lubetzky, Michelle; Lentine, Krista L.; Edusei, Emmanuel; Parsons, Ronald; Pavlakis, Martha; Woodside, Kenneth J.; Adey, Deborah; Blosser, Christopher D.; Concepcion, Beatrice P.; Friedewald, John; Wiseman, Alexander; et al.
Abstract : Kidney allograft failure and return to dialysis carry a high risk of morbidity. A practice survey was developed by the AST Kidney Pancreas Community of Practice workgroup and distributed electronically to the AST members. There were 104 respondents who represented 92 kidney transplant centers. Most survey respondents were transplant nephrologists at academic centers. The most common approach to immunosuppression management was to withdraw the antimetabolite first (73%), while only 12% responded they would withdraw calcineurin inhibitor (CNI) first. More than 60% reported that the availability of a living donor is the most important factor in their decision to taper immunosuppression, followed by risk of infection, risk of sensitization, frailty, and side effects of medications. More than half of respondents reported that embolization was either not available or offered to less than 10% as an option for surgical intervention. Majority reported that ≤50% of failed allograft patients were re‐listed before dialysis, and less than a quarter of transplant nephrologists performed frequent visits with their patients with failed kidney allograft after they return to dialysis. This survey demonstrates heterogeneity in the care of patients with a failing allograft and the need for more evidence to guide improvements in clinical practice related to transition of care. Abstract : This survey of transplant providers demonstrates heterogeneity in the care of patients with failing allografts, including immunosuppression withdrawal and the need for more evidence to optimize clinical practice related to transition of care.